2019
DOI: 10.1002/oby.22620
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abdominal Obesity in China: Results from a Cross‐Sectional Study of Nearly Half a Million Participants

Abstract: Objective This study aimed to examine the latest prevalence of abdominal obesity in China based on nationally representative data. Methods A stratified, multistage, random sampling method was used to obtain a nationally representative sample of residents aged ≥ 18 years from 31 provinces in mainland China from October 2012 to December 2015. Abdominal obesity was defined as a waist circumference ≥ 90 cm for men and a waist circumference ≥ 85 cm for women. Results The data of 441,306 participants were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 29 publications
(30 reference statements)
3
49
1
Order By: Relevance
“…Interestingly, when conducting a subgroup analysis in BMI and WC, beneficial and more significant effects were found in the subgroup of females, Asia region studies, and duration of intervention ≥6 months (all p < 0.026). Reasonable explanations for the increased effect of vitamin D treatment in special groups may be the fact that obesity prevalence among women and Asians is higher than that in men and other areas [50, 51]. In particular, Asians are more likely to have central fat deposition despite having a lower BMI [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when conducting a subgroup analysis in BMI and WC, beneficial and more significant effects were found in the subgroup of females, Asia region studies, and duration of intervention ≥6 months (all p < 0.026). Reasonable explanations for the increased effect of vitamin D treatment in special groups may be the fact that obesity prevalence among women and Asians is higher than that in men and other areas [50, 51]. In particular, Asians are more likely to have central fat deposition despite having a lower BMI [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates of CVD and cardiometabolic disorders have been reported to be high in this region. 42 , 43 , 44 This study followed the Strengthening the Reporting of Observational Studies in Epidemiology ( STROBE ) reporting guideline for cross-sectional studies. The Human Studies Committee of Sun Yat-sen University approved the study protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike in Caucasian individuals, body fat in Chinese individuals tends to accumulate in the abdominal cavity, which is more likely to result in abdominal obesity. A study based on the Chinese population showed that abdominal obesity is currently an increasing trend in China, with an adult prevalence rate of 29.1% (28.6% for men and 29.6% for women) [55]. More importantly, the prevalence rates of T2DM in the overweight and obese population in China are 12.8% and 18.5%, respectively [56].…”
Section: Effect Of Vfa On Cimt In Patients With T2dmmentioning
confidence: 99%